Representations of the natural world in Old English poetry - Neville, Jennifer, 1968- (Cambridge, U.K. ; New York : Cambridge University Press, 1999)
This book examines descriptions of the natural world in a wide range of Old English poetry. Jennifer Neville describes the physical conditions experienced by the Anglo-Saxons - the animals, diseases, landscapes, seas and weather with which they had to contend. She argues that poetic descriptions of these elements were not a reflection of the existing physical conditions but a literary device used by Anglo-Saxons to define more important issues: the state of humanity, the creation and maintenance of society, the power of individuals, the relationship between God and creation, and the power of writing to control information.
Introduction: defining the natural world -- Defining and confining humanity -- Constructing society: outside and inside, powerlessness and control -- Standing outside, standing out: defining the individual -- Representing God; power in and against nature -- Enclosing the natural world: knowledge and writing -- Conclusion.
Includes bibliographical references (pages 207-216) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: English poetry -- Old English, ca. 450-1100 -- History and criticism; Nature in literature; Poésie anglaise -- ca 450-1100 (Vieil anglais) -- Histoire et critique; Nature dans la littérature.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; English poetry -- Old English; Nature in literature; Versdichtung; Natur; Gedichten; Oudengels; Natuur; Nature -- Dans la littérature.; Poésie anglaise -- 450-1100(vieil anglais) -- Histoire et critique; Altenglisch; 450-1100; Electronic books; Criticism, interpretation, etc